2000
DOI: 10.1002/1521-4109(200012)12:18<1493::aid-elan1493>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

PMo12-Doped Carbon Ceramic Composite Electrode Based on Sol-Gel Chemistry and Its Electrocatalytic Reduction of Bromate

Abstract: A conductive carbon ceramic composite electrode (CCE) comprised of α‐type 1:12 phosphomolybdic acid (PMo12) and carbon powder in an organically modified silicate matrix was fabricated using a sol‐gel method and characterized by scanning electron microscopy, cyclic voltammetry, and Osteryoung square‐wave voltammetry. Osteryoung square‐wave voltammograms of the modified electrode immersed in different acidic aqueous solutions present the dependence of current and redox potential on pH. The PMo12‐doped CCE shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Three pairs of redox peaks i.e. I-I , II-II and III-III corresponded to the oxidation and reduction of PMo 12 through two-, four-and six-electron processes, respectively [8,9,19,48,57,58]. The formal potentials (E • = 1/2(E pa + E pc ), the mean value of the anodic and cathodic peak potentials [56]), peak separations ( E p = E pa − E pc ) and current densities for the recorded CVs are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three pairs of redox peaks i.e. I-I , II-II and III-III corresponded to the oxidation and reduction of PMo 12 through two-, four-and six-electron processes, respectively [8,9,19,48,57,58]. The formal potentials (E • = 1/2(E pa + E pc ), the mean value of the anodic and cathodic peak potentials [56]), peak separations ( E p = E pa − E pc ) and current densities for the recorded CVs are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [8,22,23,48,57,60,62,63] have shown that reduced POMs are capable of delivering electrons to other species, thus serving as powerful electron reservoirs for multielectron reductions. In our studies, we found that GCE/MWCNTs/[C 8 Py][PF 6 ]-PMo 12 shows good electrocatalytic activity for the reduction of hydrogen peroxide and iodate.…”
Section: Electrocatalytic Behavior Of Gce/mwcnts/[c 8 Py][pf 6 ]-Pmo 12mentioning
confidence: 99%
“…To verify this, the electrochemical behavior and the electrocatalytic activity of 1 were also explored in the application of bulk‐modified carbon pasted electrode (CPE) and the reduction of nitrite, respectively. As seen from Figure S15a in the Supporting Information, the cyclic voltammetric (CV) plot of 1 ‐CPE in a 1 m H 2 SO 4 solution exhibits three reversible redox peaks in the potential range from −150 to 800 mV with the mean peak potentials (i.e., E 1/2 =( E pa + E pc )/2) of 340 mV (I–I′), 175 mV (II–II′), and −45 mV (III–III′), corresponding to three consecutive two‐electron processes of the Mo atoms in 1 . On the other hand, with the addition of nitrite, the reduction peak currents increased markedly, while the oxidation peak currents decreased, thus confirming the success in the electrocatalytic reduction of nitrite (see Figure S15b in the Supporting Information) .…”
Section: Figurementioning
confidence: 99%
“…Many methods for the removal of bromate from potable water have been proposed including ion exchange [5], nanofiltration [6], UV irradiation [7], photocatalytic degradation [8], coagulation with Al 3+ and Fe 3+ [9], chemical reduction with a variety of reducing agents, such as Fe 2+ [10], biological degradation [11], as well as electrochemical reduction on various cathodes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%